Setting the Minimum: Ontario's Employment Standards in the Postwar Years, 1944-1968 - Thomas, Mark (Labour/Le Travailleur, 2004)
Abstract Minimum labour standards are legally established standards that apply to most employers and employees, and include minimum wages, maximum hours of work, overtime, and paid time off. The regulation of minimum standards in Ontario was consolidated within the Ontario Employment Standards Act in 1968. While the provincial minimum standards of the late 19th and early 20th century have been well documented, the regulation of minimum standards during the postwar period has received little scholarly attention. This paper explores the development of minimum standards legislation in Ontario from the immediate postwar years up to the enactment of the Employment Standards Act. The paper argues that social forces both internal and external to the state pressured for the enactment of comprehensive legislation to provide some statutory protection for the most vulnerable workers in the province. However, the ways in which the state negotiated the tensions associated with providing social protection for non-unionized workers, while at the same time minimizing interference in the market, severely compromised the capacity for the legislation to provide protection for the "pockets of exploitation" they were intended for. Further, this approach to minimum standards supported and reproduced patterns of gendered and racialized segmentation within a labour market that was built around the norm of the Standard Employment Relationship, and thereby ensured standards of a secondary status for workers with the least bargaining power.